Periodontal disease in pregnancy and adverse pregnancy outcomes: Progress in related mechanisms and management strategies - Nannan, Mi; Xiaoping, Lin; Ying, Jin (Frontiers in Medicine, 2022)
Periodontal disease is an inflammatory and destructive disease of tissues supporting the tooth. A large number of studies have confirmed that periodontal pathogens and their metabolites can lead to adverse pregnancy outcomes in direct or indirect ways. Adverse pregnancy outcomes, such as preterm birth, low birth weight, and preeclampsia, have a serious impact on human reproductive health. In recent years, although the level of global medical technology has gradually improved, the incidence of adverse pregnancy outcomes has not declined and is still a global public health problem. The purpose of this review is to summarize the current data on periodontal disease in pregnancy and adverse pregnancy outcomes, including the association between periodontal disease and adverse pregnancy outcomes, the pathogenic mechanism related to this association, the efficacy of different nutrition supplements for both periodontal disease and adverse pregnancy outcomes and the effect of providing periodontal treatment on the occurrence of adverse pregnancy outcomes, to provide guidance for the prevention and treatment of adverse pregnancy outcomes in clinical practice.